Environmental Monitoring of Zoonotic Fungal Infection in Broiler Chickens: Novel Approach to Control using Nano-fungicide Composite - A. N. Mohammed; G. K. Abdel-Latef (Faculty of Animal Science, Bogor Agricultural University, 2021)
Control of fungal infections has not taken much attention compared to bacterial and viral pathogens inflicting significant economic losses to the poultry sectors as well as direct harms to human health due to their zoonotic implication. This study aimed to investigate the existence of fungal pathogens in broiler chicks dropping and their environment. As well, evaluate the efficiency of Terminator disinfectant (coco-benzyl-dimethyl ammonium chlorides and glutaraldehyde), nano copper oxide (CuO NPs), and Terminator/ nano copper oxide (Terminator/CuO NPs) on the fungal growth inhibition to control resistant fungus to antifungal agents. All samples (n= 320) were collected from chicks dropping, their environment (air, water, feeds, litter, drinkers, and feeders) as well, the attendant’s hand swabs for isolation and identification of fungal pathogens. The susceptibility pattern of 65 strains of fungal isolates to antifungal agents, terminator disinfectant, and nano-fungicide composites was determined by the disc diffusion assay and broth micro-dilution method. All isolates were highly resistant to voriconazole antifungal drugs, whilst Aspergillus fumigatus (A. fumigatus) was resistant (100%) to fluconazole. Furthermore, the sensitivity of Aspergillus terreus (A. terreus) and Penicillium corylophilum (P. corylophilum) was 0.0% to fluconazole, and amphotericin-B. Whilst the antifungal activity of Terminator/CuO NPs against fungal pathogens proved its lethal effect (100%) against all fungal isolates at 0.5 mg/mL compared to the efficiency of both Terminator at 1:50 and CuO NPs at 2.0 mg/mL was not exceeded 84.6% and 76.9%, respectively against all fungal strains. In conclusion, nano-fungicide is a promising product for the prevention of fungal pathogens in broiler chickens and their environment. The control of zoonotic resistant fungus using novel nano-fungicide composite (Terminator/CuO NPs) at 0.5 mg/mL concentration was efficiently achieved compared to nano copper oxide at 2.0 mg/mL.